Protective Effects of Melatonin on Methamphetamine-Induced Blood–Brain Barrier Dysfunction in Rat Model - Jatuporn Namyen (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. The specialized brain endothelial cells interconnected by unique junctions and adhesion molecules are distinctive features of the blood–brain barrier (BBB), maintaining the homeostasis of the cerebral microenvironment. This study was designed to investigate the protective effects of melatonin on methamphetamine (METH)-induced alterations of BBB integrity. Wistar rats were randomly distributed into groups and underwent melatonin pretreatment and escalating-high doses of METH treatment. Immunohistochemistry was performed to demonstrate the BBB leakage. Protein and RNA samples were isolated from hippocampal and prefrontal cortical tissues and measured expression levels of molecular markers associated with BBB structural components and inflammatory processes. METH provoked the loss of zonula occludens (ZO)-1, occludin, and claudin-5 tight junction proteins. Furthermore, METH caused an excessive increase in matrix metalloproteinase-9 (MMP-9) enzyme, intercellular adhesion molecule 1 (ICAM-1), and vascular cell adhesion molecule 1 (VCAM-1) and the increase in NAD(P)H oxidase 2 (NOX2). Melatonin exerted the protective effects by recovering tight junction loss; attenuating excessive MMP-9, NOX2, and cell adhesion molecule expression; and reducing serum albumin in the brain. Our results also showed the protective effects of melatonin against METH neurotoxic profiles, characterized by reactive gliosis: microglia (integrin-αM) and astrocyte (GFAP); an excessive upregulation of primary pro-inflammatory cytokines: interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α); activation of neuroinflammatory signaling: nuclear factor-kappa B (NF-κB); and suppression of anti-oxidative signaling: nuclear factor erythroid 2-related factor (Nrf2), that may exacerbate BBB structural impairment. Our results provide insights into the beneficial effects of melatonin against METH-induced BBB disruption and mechanisms that play detrimental roles in BBB impairment by in vivo design.